2016
DOI: 10.1590/2317-1545v38n4159502
|View full text |Cite
|
Sign up to set email alerts
|

Sodium hypochlorite for removal of the sarcotesta from newly extracted and stored papaya seeds

Abstract: -The objective of this study was to evaluate the effect of sodium hypochlorite on removal of the sarcotesta and the germination process of newly harvested papaya seeds before and after storage for 44 days. Nine treatments were evaluated using a completely randomized design with six treatments in a split plot arrangement and three additional treatments (control), each treatment with eight replications. The plots consisted of methods for breaking dormancy: M1 -sieve method + drying to 7%, M2 -sieve method + dryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…However, papaya generally suffers from several quality issues, such as different sizes and low germination rate at the initial stage [1,5]. The low and irregular germination percentage of papaya seeds can be attributed to the seed encapsulated within sarcotesta (aril, or outer seed coat forms the outer integument), preventing the seed germination [3,5,6]. In other cases, the dormancy was still reported after removing sarcotesta because of the presence of phenolic compounds and phytohormones inside sarcotesta, which acts as an inhibitor in germination [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, papaya generally suffers from several quality issues, such as different sizes and low germination rate at the initial stage [1,5]. The low and irregular germination percentage of papaya seeds can be attributed to the seed encapsulated within sarcotesta (aril, or outer seed coat forms the outer integument), preventing the seed germination [3,5,6]. In other cases, the dormancy was still reported after removing sarcotesta because of the presence of phenolic compounds and phytohormones inside sarcotesta, which acts as an inhibitor in germination [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The low and irregular germination percentage of papaya seeds can be attributed to the seed encapsulated within sarcotesta (aril, or outer seed coat forms the outer integument), preventing the seed germination [3,5,6]. In other cases, the dormancy was still reported after removing sarcotesta because of the presence of phenolic compounds and phytohormones inside sarcotesta, which acts as an inhibitor in germination [3,5,6]. Besides, other factors affect the germination rates of papaya, namely, moisture content, temperature, light, and storage time of seeds [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcotesta yang tetap dipertahankan selama proses pengeringan benih menimbulkan induksi dormansi (Zainudin and Adini, 2019). Aplikasi NaOCl pada benih Carica mampu mengatasi sarcotesta namun berdampak negatif terhadap daya kecambah benih dibandingkan dengan dilakukan pengeringan sampai kadar air benih 7% dengan hasil masing-masing 88% dan 35% (Jesus et al, 2016). Perlakuan pematahan dormansi yang efektif perlu dikembangkan untuk mengatasi kendala dalam perkecambahan yang mempunyai viabilitas rendah.…”
Section: Pendahuluanunclassified
“…The location of the seed inside the fruit may influence its internal morphology, thereby affecting the physical and physiological quality. According to Jesus et al (2016), at this stage, the removal of the sarcotesta may simultaneously promote the removal of compounds that could be used at the later stages by seeds for structuring the cell walls and/or the germ-promoting substances in sarcotesta, endosperm and embryo during the germination. We found that the resting in the laboratory environment at room temperature induced the maximum seed germinability (Tables 1 and 2), which would presumably be associated with a change between the promoters and inhibitors of germination caused by presence of seeds inside the fruit during the ripening phase.…”
Section: Physiological Seed Qualitymentioning
confidence: 99%